2016
DOI: 10.1007/s11033-016-4026-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression analysis, cloning and characterization of the 5′-regulatory region of the bovine FABP3 gene

Abstract: Fatty acid binding protein 3 (FABP3) is a member of the FABP family which bind fatty acids and have an important role in fatty acid metabolism. A large number of studies have shown that the genetic polymorphisms of FABP3 are positively correlated with intramuscular fat (IMF) content in domestic animals, however, the function and transcriptional characteristics of FABP3 in cattle remain unclear. Real-time PCR analysis revealed that bovine FABP3 was highly expressed in cardiac tissue. The 5'-regulatory region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…RACE ready 5′-end first strand cDNA was synthesized through SMARTer RACE 5′ Kit (Takara, Beijing, China) PCR was performed for the amplification of RACE ready cDNA using two different gene specific reverse primers (Table S2) located between exon 1 and 2 of the TORC2 gene and Universal Primer A Mix (Takara, Beijing, China) was used as forward primer. Nested PCR was conducted with the conditions as mentioned previously [79,80] using SeqAmp DNA polymerase PCR enzyme (Clontech Inc., CA, USA). Touchdown PCR was performed with the conditions of five cycles at 94 °C for 30 s, 72 °C for 3 min; then, five cycles at 94 °C for 30 s, 70 °C for 30 s, 72 °C for 3 min, and; 25 cycles at 94 °C for 30 s, 68 °C for 30 s and 72 °C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…RACE ready 5′-end first strand cDNA was synthesized through SMARTer RACE 5′ Kit (Takara, Beijing, China) PCR was performed for the amplification of RACE ready cDNA using two different gene specific reverse primers (Table S2) located between exon 1 and 2 of the TORC2 gene and Universal Primer A Mix (Takara, Beijing, China) was used as forward primer. Nested PCR was conducted with the conditions as mentioned previously [79,80] using SeqAmp DNA polymerase PCR enzyme (Clontech Inc., CA, USA). Touchdown PCR was performed with the conditions of five cycles at 94 °C for 30 s, 72 °C for 3 min; then, five cycles at 94 °C for 30 s, 70 °C for 30 s, 72 °C for 3 min, and; 25 cycles at 94 °C for 30 s, 68 °C for 30 s and 72 °C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that the storage and distribution of fat are related to age, sex, hormones, fat synthesis, fat decomposition transport, and other factors [9‐12]. Among these factors, fatty acid‐binding proteins (FABPs) are critical mediators of fat storage and distribution [13‐16] that bind fatty acids and other lipid ligands. Epidermal FABPs (EFABPs) are differentially expressed between human omental and subcutaneous adipose tissue [11], and elevated levels of adipocyte FABPs (AFABPs) have been found in pericardial fat tissue and are associated with cardiac dysfunction in obese people [17].…”
Section: Fabpsa Organisms Lfabp (Fabp1) Ifabp (Fabp2) Hfabp (Fabp3)mentioning
confidence: 99%
“…Thus, the upregulation of LPL and FABP3 due to overexpression of CREB1 suggested that it can also help control exogenous uptake and intracellular channeling of FA. The promoter sequence of FABP3 has a CREB binding site and is highly conserved in cattle, sheep and pigs [ 32 ]. Taken together, these results indicate that CREB may play a role in lipogenesis in goat mammary gland as in non-ruminants.…”
Section: Discussionmentioning
confidence: 99%